Construction and simulation bias study of the guide Tube Calibration System for JUNO. (8th July 2021) - Guo, Yuhang; Zhu, Kangfu; Zhang, Qingmin; Zhang, Feiyang; Meng, Yue; Liu, Jianglai; Qu, Eryuan
Abstract: A Guide Tube Calibration System (GTCS) has been designed for the Jiangmen Underground Neutrino Observatory (JUNO), in order to measure the detector energy response near the outer radius of the active volume. Recently, a prototype system has been constructed and tested, and the calibration algorithm has also been studied to evaluate the risk when the simulation tuning and the error control fail. In this paper, we first report its construction and the performance tests in the lab. Then the influence on the global energy measurement caused by the simulation bias of GTCS is discussed, in order to make sure the algorithm is qualified.